Development of Novel Alumina by Solid-State Reaction for 99Mo/99mTc Adsorbent Material - Munir, Miftakul; Lestari, Enny; Hambali, Hambali; Kadarisman, Kadarisman; Marlina, Marlina (Al-Kimia, 2019)
Technetium-99m (99mTc), a daughter radionuclide of molybdenum-99 (99Mo), is the most widely used radiodiagnostic agent due to its ideal characteristics. The separation of this radionuclide from 99Mo is commonly performed using alumina. However, a new production method of this radionuclide, which employs a low specific activity 99Mo, makes alumina no longer suitable as separation material. This study aims to develop novel alumina using a facile solid-state reaction for 99Mo/99mTc generator system. The SS-alumina was synthesized from aluminium nitrate nonahydrate and ammonium bicarbonate without solvent. The resulted SS-alumina was then analyzed by FTIR and BET method. 99Mo adsorption and 99mTc releasing study on a series of pH were also performed. FTIR study revealed that the resulting material was Al2O3 with a surface area of 237.65 m2/g. The adsorption capacity, 99mTc yield, 99Mo breakthrough, and alumina breakthrough were 76.06 mg Mo/g alumina, 80.31%, 56.5 µCi/mCi 99mTc, and less than 5 mg/mL, respectively. The elution profile shows a high activity of 99mTc in 2nd and 3rd fraction. It is concluded that the SS-alumina shows good performance as adsorbent material for separation of a 99Mo/99mTc and further work is now underway.